STATISTICAL ASSESSMENT OF THE EFECTIVA EMPLOYMENT OF THE POPULATION IN THE REPUBLIC OF UZBEKISTAN - Akbarova Zaripa (American Journals, 2025)
When analyzing the labor market, it is important to quantify the relationship between the employed population and general indicators that reflect the development of the economy. To do this, the number of people employed in the economy and the factors affecting this indicator, as well as forecast values, were determined. In this regard, it is important to create multifactorial econometric models based on the study of the labor market of our country, taking into account the factors affecting the employment rate.
Keywords: Labor market, employment, unemployment, average nominal wages, sums, volume of capital investments.